Assessment of Neonatal Cord Blood SARS-CoV-2 Antibodies after COVID-19 Vaccination in Pregnancy: A Prospective Cohort Study - Sourouni, Marina; Braun, Janina; Oelmeier, Kathrin; Möllers, Mareike; Willy, Daniela; Hennies, Marc T.; Köster, Helen Ann; Pecks, Ulrich; Klockenbusch, Walter; Schmitz, Ralf (Geburtshilfe und Frauenheilkunde, 2022)
Introduction Maternally derived antibodies are a key element of neonatal immunity. So far, limited data has shown transplacental transmission of antibodies after coronavirus disease 2019 (COVID-19) vaccination with BNT162b2 in the third trimester. Our aim was to detect vertically transferred immunity after COVID-19 vaccination with BNT162b2 (Comirnaty, BioNTech-Pfizer) or mRNA-1273 (Spikevax, Moderna) in the first, second or third trimester of pregnancy, and investigate the impact of maternal characteristics on umbilical cord antibody titre in newborns after delivery.Study Design Women who gave birth in our department and were vaccinated against COVID-19 during pregnancy were enrolled in CRONOS Satellite, a subproject of the German COVID-19-Related Obstetric and Neonatal Outcome Study. The titre of immunoglobulin G (IgG) antibodies to the receptor-binding domain of the SARS-CoV-2 spike protein was quantified in umbilical cord blood using the SARS-CoV-2 IgG II Quant immunoassay. Correlations between antibody titre and variables, including week of pregnancy when vaccinated, interval between vaccination and delivery, age and body mass index (BMI) were assessed with Spearmanʼs rank correlation. A follow-up was conducted by phone interview 4 – 6 weeks after delivery.Results The study cohort consisted of 70 women and their 74 newborns. Vaccine-generated antibodies were present in all samples, irrespective of the vaccination type or time of vaccination. None of the parameters of interest showed a meaningful correlation with cord blood antibody concentrations (rho values < 0.5). No adverse outcomes (including foetal malformation) were reported, even after vaccination in the first trimester.Conclusions Transplacental passage of SARS-CoV-2 antibodies from mother to child was demonstrated in all cases in the present study. It can therefore be assumed that the newborns of mothers vaccinated at any time during pregnancy receive antibodies via the placenta which potentially provide them with protection against COVID-19. This is an additional argument when counselling pregnant women about vaccination in pregnancy.
Keywords: SARS-CoV-2 vaccine; pregnancy; booster shot; vertical immunity